United States local health department engagement in activities that support active transportation considerations in land use and transportation policies: Results of a national survey - Sreedhara, Meera; Goins, Karin Valentine; Frisard, Christine; Lemon, Stephenie C. (Frontiers in Environmental Science, 2022)
Active transportation by walking or biking can improve health and quality of life. Public health official participation in transportation and land use policy-related decision-making is recommended to improve opportunities for active transportation. However, U.S. local health department (LHD) engagement in activities that support this decision-making is not well understood. The purpose of this study was to describe engagement in activities that support inclusion of active transportation in transportation and land use decision-making among small and midsize LHDs, identify LHD characteristics associated with engagement, and describe interest in training activities to increase engagement. Data are from a 2017 national probability cross-sectional survey of U.S. LHDs serving fewer than 500,000 residents assessed departmental engagement in eleven activities related to ten cross-cutting capabilities that support engagement in transportation and land use decision-making (30.2% response rate). Negative binomial regression of 183 LHDs with complete data determined the relationship between LHD characteristics and engagement in activities. Survey weights were applied to generate nationally representative statistics. LHDs reported their engagement in eleven activities that support active transportation in land use and transportation decision-making as a major responsibility, secondary responsibility, or neither. Responses were summed to generate a score. LHDs reporting major responsibility varied by activity and ranged from 8.6% for data and assessment to 32.7% for public outreach to community. The distribution of engagement scores was skewed (mean=6.2, variance=34.7). Larger population size served, any staff working on active transportation issues, and contracting with an individual/organization on active transportation were significantly associated with greater engagement in activities related to land use and transportation decision-making that support active transportation. High interest in training or technical assistance for activities ranged from 12.2% for dedicated staffing to 42.8% for public outreach to community. These data demonstrate room for improvement in activities and capabilities supportive of active transportation in land use and transportation decision-making and modest but promising interest in assistance for greater engagement among LHDs.